The geographical scales of fear: spatiality of emotions, emotional spatialities - Sági, Mirjam (Hungarian Geographical Bulletin, 2022)
A multi-scalar understanding of fear has not been completely absent from geographical theory, however, it has not been given the attention it deserves and definitely has not been utilised in empirical research to the extent it has explanatory power to our globalised world infused with fears. By a multi-scalar understanding I refer to geographical scale as social production or social construction following critical geographers, who see the relationship between these scales as non-hierarchical. This paper draws on and combines theoretical works understanding fear as a socially and politically produced emotion that is politically exploited – most often through Othering – and operates on multiple geographical scales. It is an everyday experience that is produced and made sense across the scales of the body, home, neighbourhood, city, nation, region, supranational unions, the global scale and beyond. This paper draws together three particular areas concerning fear related research; (1) it emphasises that fear is an emotion; but (2) it is deeply embedded in social, economic, political and spatial relations and often closely linked to – if not dependent on – Othering and marginalisation; and (3) fear is reproduced in a transscalar way at all geographical scales. By drawing together these three interlinked approaches to fear, on the one hand, this paper aims to contribute to the literature by demonstrating the way the “us” versus “them” nexus is reimagined at different scales according to political convenience. On the other, it hopes to inspire more research in the field of emotional geography in general and that of fear in particular in Hungary (and more broadly in the CEE region), where this sub-field has been underrepresented even though its great explanatory potentials.